(untitled) (Research, Society and Development, 2022)
Introduction: Coronavirus infection spread rapidly throughout the world and as a preventive measure, social isolation was implemented, causing psychological reactions and emotional and mental impact. Objective: Analyze population during coronavirus pandemic, elucidating its consequences on mental health. Method: Integrative review carried out during February 2021, in Scientific Electronic Library Online (SciELO) and Pubmed databases using the descriptors “mental health and Covid-19 quarantine”. Results: Among the materials accessed, 43 articles were analyzed, systematized according to the population studied: children and adolescents, adults, elderly people and unspecified. Discussion: In children, social isolation is harmful, as some body systems have not been fully developed. In adults, it shows an increase in depression and stress mainly in males. Health care professionals are more susceptible to burnout and substance abuse. Conclusion: There is no doubt that quarantine during Covid-19 pandemic brought numerous repercussions for everyone’s mental health, such as anxiety, depression and post-traumatic stress, but in order to have a greater dimension of the impact of social isolation, it is necessary to increase studies addressing the impacts on the mental health, especially in elderly people.